(untitled) (American Journal of Multidisciplinary Research and Innovation, 2022)
The Department of Education is delving into instructional material development to support students learning. This study aimed to develop Infographics in Guided Discovery Lessons (IGDL) for Grade 6 Science. It investigated the learning competencies in Science 6 that can be best taught using infographics as perceived by teachers. Also, it determined the effectiveness in improving the performance among the learners. The study used the descriptive research design employing research and development methodology. It surveyed 162 Science teachers from the Schools Division of Ilocos Norte on the essential competencies using needs assessment survey. The developed infographics was validated by experts and tried out to the Grade 6 pupils of San Nicolas Elementary School. A researcher-made pretest and posttest were used to determine the effectiveness of the infographics. Result showed that 46.67% of the Science 6 learning competencies were best taught using infographics. The Learning Resource Management and Development System Evaluation Tool for Print Materials was utilized for the content validity of the IGDL. In terms of content, instructional and technical qualities, the IGDL was evaluated as valid. This implies that IGDL can be utilized in the acquisition of Science concepts. The tryout result revealed that the level of performance of learners improved from needs improvement to very satisfactory level. T-test showed a significant difference between the level of performance of the Grade 6 learners in the pretest and posttest mean scores. Thus, the IGDL improved the students’ performance, and it can be used as instructional material in teaching concepts in Science.